How fair is workfare?: gender, public works, and employment in rural Ethiopia - Quisumbing, Agnes R. (International Food Policy Research Institute, 2005)
...Workfare programmes have been used across Asia, Africa, and Latin America to provide the poor with income transfers, help them cope with income shocks, and create assets by constructing much-needed infrastructure—which, once built, can continue to generate employment. Recently, policymakers have begun paying attention to gender issues in workfare programmes... The authors of this brief used the Ethiopian Rural Household Survey (ERHS) to explore gender dimensions of public works programmes... The ERHS results imply that food for-work programmes have a number of levers to increase the participation of women.